Parameter estimation for a computable general equilibrium model: a maximum entropy approach - Arndt, Channing; Robinson, Sherman; Tarp, Finn (Elsevier, 2002)
The authors introduce a maximum entropy approach to parameter estimation for computable general equilibrium (CGE) models. The approach applies information theory to estimating a system of nonlinear simultaneous equations. It has a number of advantages. First, it imposes all general equilibrium constraints. Second, it permits incorporation of prior information on parameter values. Third, it can be applied in the absence of copious data. Finally, it supplies measures of the capacity of the model to reproduce the historical record and the statistical significance of parameter estimates. The method is applied to estimating a CGE model of Mozambique."-- from Abstract.